Arm orthosis modeling for exploration of human-robot interaction in arm reaching trajectory formation - Zadravec, Matjaž (Informatica Medica Slovenica, 2012)
Arm reaching robotic training is usually programmed in a way to assist patients by facilitating movements along a straight line from the chosen starting to the target point. But if we take into account the muscular condition of the patient's upper limb, the trajectories might be different. The key is to find an optimal trajectory. The article presents experimental planar arm reaching movement trajectories obtained by instructing one healthy subject to move the hand from the selected starting to the target point in a relatively narrow workspace. The subject carried an arm orthosis to which we attached elastic bands emulating muscle tightness condition. The results show clear deviations of the trajectories when elastic bands were attached to the orthosis as compared to the uninhibited ones. Clear understanding of human arm motion will aid in better human-machine interaction.
Keywords: Arm; interakcija človek-stroj; Robotics; robotika; roka; zgornji ud